Transformasi Digital Manajemen Aset Infrastruktur: Optimalisasi Operasional PDAM melalui Sistem Pelacakan QR Code Berbasis Web - Indra Putra Mahayudi; Zikri Ezza Alhira; Triase, Triase (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2025)
Pipeline network operations require fast and accurate asset identification, but manual processes in the field often cause delays in recording and data errors, contributing to increased Non-Revenue Water (NRW) levels. This article designs and evaluates a QR code-based pipeline asset management information system at Perumda/PDAM Tirtanadi to accelerate identification, organize history tracking, and improve maintenance information quality. The Rapid Application Development (RAD) approach was selected for its ability to accommodate dynamic operational requirements through iterative stakeholder involvement, reducing system failure risks compared to conventional waterfall methods. Qualitative data from field observations and structured interviews with operational staff were systematically transformed into Functional Requirement Specifications through requirement engineering frameworks. Functional evaluation was conducted through black-box testing and field workflow trials to assess scanning reliability, ease of use, and data consistency. The results demonstrate that the system operates stably with 100% functional test success rate, significantly improves asset traceability through real-time QR code scanning, and facilitates data-driven maintenance decision-making. Performance analysis indicates that QR code scanning reduces asset identification time by approximately 75% compared to manual document searching. The Model-View-Controller (MVC) architecture ensures system scalability for future Geographic Information System (GIS) integration. Further implementation is directed at GIS integration, refinement of data access policies in accordance with the Personal Data Protection Law (UU PDP), and expansion of coverage to other operational units. Thus, this system not only improves operational efficiency but also contributes to reducing water loss through faster damage handling, serving as a replicable model for other water utilities implementing technology-based asset management.